Scale development of apparel customization brand value: From the perspectives of practitioners and consumers - Li, Hao; Gu, Li-Wen; Liu, Xiao-Gang; Ruan, Yan-Wen (Frontiers in Psychology, 2022)
China apparel customization brands (CACBs) have been recently growing in massive quantities despite being in their infancy stages of brand value building. Although scholars have proven brand value’s importance in sustainable brand growth, studies on the specific context of CACBs are still limited. This research proposes a conceptual framework of CACBs’ brand value measured dimension based on previous studies and divides brand value into both general and specific dimensions. Accordingly, qualitative (semi-structured interviews) and quantitative (online survey) studies were conducted from the perspectives of practitioners and consumers. Ultimately, a scale of 30 items with 9 dimensions was generated. Results reveal that brand association in the general dimensions and brand service in the special dimensions were the largest promoters of CACB brand value. Hence, practitioners should pay more attention to dimensions of cognitive conflicts. Practical suggestions for apparel customization marketers are proposed to build and enhance brand value.